Diversification of Higher Education in Vietnam: Experiences in International Cooperation and Financial Autonomy at the VNU-International School - Nguyễn, Trọng Do (H. : ĐHQGHN, 2017)
VNU Journal of Science: Education Research ; Vol. 32,No. 1 (2016) ; p. 1-9